2009
DOI: 10.1103/physreva.80.062109
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Zeno switch for single-photon coherent transport

Abstract: Using a dynamical quantum Zeno effect, we propose a general approach to control the coupling between a two-level system (TLS) and its surroundings, by modulating the energy level spacing of the TLS with a high frequency signal. We show that the TLS--surroundings interaction can be turned on or off when the ratio between the amplitude and the frequency of the modulating field is adjusted to be a zero of a Bessel function. The quantum Zeno effect of the TLS can also be observed by the vanishing of the photon ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 40 publications
1
100
0
Order By: Relevance
“…The strong-coupling regime has been realized in the classic cavity quantum electrodynamics (QED) systems [10][11][12], as well as in circuit QED experiments [13][14][15][16]. Several experimental systems have been proposed for realizing devices such as a single-photon transistor [4,8] and a quantum switch [6,7,17], including surface plasmons coupled to a single two-level emitter [4], a superconducting transmission line resonator coupled to a local superconducting charge qubit [6,7], and propagating photons in a one-dimensional (1D) waveguide coupled to a TLS [18,19]. Most of the theoretical work focuses on a single-photon coupled to a local quantum system modeled as a TLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong-coupling regime has been realized in the classic cavity quantum electrodynamics (QED) systems [10][11][12], as well as in circuit QED experiments [13][14][15][16]. Several experimental systems have been proposed for realizing devices such as a single-photon transistor [4,8] and a quantum switch [6,7,17], including surface plasmons coupled to a single two-level emitter [4], a superconducting transmission line resonator coupled to a local superconducting charge qubit [6,7], and propagating photons in a one-dimensional (1D) waveguide coupled to a TLS [18,19]. Most of the theoretical work focuses on a single-photon coupled to a local quantum system modeled as a TLS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing interest in designing quantum optical elements based on the strong coupling between light and matter [1][2][3][4][5][6][7][8][9]. The strong-coupling regime has been realized in the classic cavity quantum electrodynamics (QED) systems [10][11][12], as well as in circuit QED experiments [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this kind of manipulation can be achieved by coupling a 1D waveguide with a node where the transmission and reflection of the photons can be potentially controlled [1][2][3][4][5][6][7][8][9]. It had been shown that the two-photon transport is strongly correlated in 1D waveguide coupled to a two-level system [1,2] where the strong correlation arises from the interference between the reemitted and scattered waves in the 1D waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these models are formed by an array of cavities with each cavity containing one or more atoms [15], where photons hop between the cavities. Recently, due to the potential use for building a quantum switch for routing single-photons in quantum network, systems with one or two atoms inside the array of cavities have been extensively studied to revealed the intriguing features of photon transport in low dimensional environments [16][17][18][19][20]. It is found that the switch is formed by the interference between the spontaneous emission from atoms and the propagating modes in the one-dimensional (1D) continuum.…”
Section: Introductionmentioning
confidence: 99%